Strategi Humas Polres Pagaralam dalam Mensosialisasikan Pencegahan Pencurian Kendaraan Bermotor - Syahir Badrudin; Anita Trisiah; Deska Hariyanti (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2017)
This research was conducted to explain Pagaralam Polres Public Relations Strategy in preventing motor vehicle theft in Pagaralam City. Pagaralam Police elected as the subject of research, because this institution is a legal institution that runs and regulates crime laws and is definitely daily with the community. To carry out communication activities related to the danger of motor vehicle theft in order to run properly then the need for a strategy so that the implementation of activities will be more focused. Therefore thesis is made by the author with the title '' Public Relations Strategy Pagaralam Police In Disseminating the Prevention of Motor Vehicle Theft '' is used to know the way public relations strategy Polres Pagaralam. This research use descriptive qualitative research method, primary informer in this research is example of Polres Pagaralam public relation. While the secondary informants are the people of Pagaralam City who live in some areas or districts. Collecting data based on results, observation and literature study. While to analyze data using descriptive analysis method, describe data obtained through reality and actual phenomenon. With the aim to know how stratib PR is done public relations Polres Pagaralam. Along with the formulation of existing problems in this thesis research, then the results of research shows public relations strategy in disseminating the prevention of vehicle theft being done Public Relations Police Pagaralam. Based on indicators of situational hatching assessment, goal setting, and overall communication have been going well.